Local Agricultural Resource Development Strategy Towards SDGs-18 Villages in West Aceh Regency - Macella, Agatha Debby Reiza; Mardhiah, Nellis; Hajad, Vellayati; Husna, Cut Asmaul; Aziz, Chairul Iqbal (Universitas Riau Kepulauan, 2026)
West Aceh Regency is a highly strategic agro-based region located in the western part of Aceh Province. This regency has abundant natural resources, particularly rice fields in the subdistricts of Kaway XVI, Woyla, Wayla Barat, Panteun Reu, Arongan, and Samatiga, which are the most extensive compared to other regions. The objective of this research is to realize the implementation of government policies and the Keujruen Blang customary institution in accordance with Qanun No. 10 of 2008 concerning the Aceh Customary Institution in order to achieve the SDGs Goal-I8 development targets. The organizational pattern within the traditional farmer institution is a coordination system in the management of rice fields from the planning stage, organization, evaluation, and monitoring, as well as the improvement of the socio-economic development of farmer groups in West Aceh Regency.The potential results of this research can be used as a reference or input and recommendation for the West Aceh Regency government in implementing a policy system for developing local wisdom resources in organizing adaptive and dynamic indigenous farmer institutions in a sustainable manner in West Aceh Regency. Based on the research results, there are four government resource strategies in planning agriculture based on local wisdom in the socio-cultural elements of agriculture. The legality of the Keujreun blang customary institution in agricultural governance can be empowered through the development of science and technology-based agriculture as well as increased involvement of customary institutions in decision-making for dynamic and adaptive strategic agricultural plans in village development.